Guided Internet-Based Treatments in Psychiatry - Lindefors, Nils; Andersson, Gerhard (Springer International Publishing : Imprint: Springer, 2016)
This book provides a practically oriented overview of internet-based treatments in psychiatry and mental health care, which represent a relatively new research area and offer a novel clinical approach. The principal focus is on internet-based cognitive behavior therapy, as this is currently the best example of evidence-based internet interventions in the field. Applications are described in a wide range of conditions, including, for example, depression, panic disorder, anxiety disorders, obsessive-compulsive disorder, post-traumatic stress disorder, eating disorders and addictions. Research background, clinical trials and evidence for efficacy and effectiveness are discussed and helpful case descriptions, provided. Information is also included on cost-effectiveness and other relevant aspects of health economics and on new technologies and future challenges. Guided Internet-Based Treatments in Psychiatry will be of great interest for practitioners and researchers alike.